(untitled) (Journal of Digital Business and Information Technology, 2024)
Cocoa plant diseases have a detrimental impact on farmers and cultivators. This is due to the limited number and working hours of cocoa plant experts. Another thing is that there are quite a lot of farmers who want to consult, which results in less than optimal handling of cocoa diseases. Therefore, researchers developed an expert system to help diagnose and provide solutions based on disease symptoms experienced by cocoa plants, so that farmers do not need to consult directly with experts. This research uses the forward chaining method in preparing rules and adds the certainty factor (CF) method to calculate the certainty value so that the resulting decisions are more accurate. From the results of manual calculations using a sample of one disease with code P1, the trial showed an accuracy value of 93.0736%. Apart from that, the system was proven to work well and was able to make diagnoses based on symptoms on cocoa plants.